Synthesis, spectral characterisation, morphology, biological activity and DNA cleavage studies of metal complexes with chromone Schiff base - P. Kavitha; K. Laxma Reddy (Arabian Journal of Chemistry, 2016)
Cu(II), Co(II), Ni(II) and Zn(II) complexes have been synthesized using 3-((pyridine-2-ylimino)methyl)-4H-chromen-4-one as a ligand derived from 3-formyl chromone and 2-amino pyridine. All the complexes were characterised by analytical, conductivity, IR, electronic, magnetic, ESR, thermal, powder XRD and SEM studies. The analytical data revealed that the metal to ligand molar ratio is 1:2 in all the complexes. Molar conductivity data indicates that all the complexes are neutral in nature. On the basis of magnetic and electronic spectral data, octahedral geometry is proposed for all the complexes. Thermal behaviour of the synthesized complexes indicates the coordinated and lattice water molecules are present in the complexes. The X-ray diffraction data suggest a triclinic system for all compounds. Different surface morphologies were identified from SEM micrographs. All metal complexes exhibit fluorescence. The antimicrobial and nematicidal activity data show that metal complexes are more potent than the parent ligand. The DNA cleavage activity of the ligand and its metal complexes were observed in the presence of H2O2.